(untitled) (The South East European Journal of Economics and Business, 2026)
This study investigates how work-related emotional burnout and work stress influence employees’ impulsive buying behaviors, focusing on the mediating role of self-control. By bridging the fields of consumer behavior and organisational studies, the research sheds light on how stress and burnout at work can spill over into personal consumption decisions. Data were collected from 1,228 employees across Turkey using established psychometric scales, and the hypotheses were tested through structural equation modelling. The results show that both emotional burnout and work stress significantly increase impulsive buying tendencies. More importantly, self-control emerged as a key factor in this relationship, suggesting that decreased self-control under stress and burnout leads to more impulsive purchasing behavior. These findings contribute to the literature by highlighting the psychological mechanisms that link work-related stress to consumer behavior, an area that has not been extensively explored. The study concludes by discussing implications for workplace interventions and suggesting avenues for future research to deepen our understanding of how occupational well-being influences financial decisions.